Sol-gel Based Nanoceramic Materials: Preparation, Properties and Applications - Mishra, Ajay Kumar; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book summarizes recent research and development in the field of nanostructured ceramics and their composites. It presents selected examples of ceramic materials with special electronic, catalytic and optical properties and exceptional mechanical characteristics. A special focus is on sol-gel based and organic-inorganic hybrid nanoceramic materials. The book highlights examples for preparation techniques including scale-up, properties of smart ceramic composites, and applications including e.g. waste water treatment, heavy metal removal, sensors, electronic devices and fuel cells. Recent challenges are addressed and potential solutions are suggested for these. This book hence addresses chemists, materials scientists, and engineers, working with nanoceramic materials and on their applications.
Nanoceramics: Fundamentals and advanced perspectives -- Advance techniques for the synthesis of nanostructured zirconia based ceramics for thermal barrier application -- Synthesis of nanostructure ceramics and their composites -- Structure, Stabilities and Electronic Properties of Smart Ceramic Composites -- Advancement of glass ceramic materials for photonic applications -- Ceramic Nanocomposites for Solid Oxide Fuel Cells -- A Review of Nanoceramic Materials for use in Ceramic Matrix Composites -- Application of Hydroxyapatite-based Nanoceramics in Wastewater Treatment: Synthesis, Characterization and Optimization -- Sol-gel derived organic-inorganic hybrid ceramic materials for heavy metal removal -- Hybrid ceramic materials for environmental applications.
Keywords: Ceramic materials; Nanochemistry; Microtechnology; Microelectromechanical systems; Refuse and refuse disposal; Ceramics; Nanochemistry; Microsystems and MEMS; Waste Management/Waste Technology